A Critical Analysis of Mobility Management Related Issues of Wireless Sensor Networks in Cyber Physical Systems - Al-Muhtadi, Jalal; Qiang, Ma; Zeb, Khan; Chaudhry, Junaid; Saleem, Kashif; Derhab, Abdelouahid; Orgun, Mehmet A.; Shankaran, Rajan; Imran, Muhammad; Pasha, Maruf (IEEE access, 2018)
Mobility management has been a long-standing issue in mobile wireless sensor networks and especially in the context of cyber physical systems; its implications are immense. This paper presents a critical analysis of the current approaches to mobility management by evaluating them against a set of criteria which are essentially inherent characteristics of such systems on which these approaches are expected to provide acceptable performance. We summarize these characteristics by using a quadruple set of metrics. Additionally, using this set we classify the various approaches to mobility management that are discussed in this paper. Finally, the paper concludes by reviewing the main findings and providing suggestions that will be helpful to guide future research efforts in the area.